158k views
1 vote
Solve 4x - 2x + 8 = 6(x + 4)

User Mic Fung
by
5.2k points

1 Answer

4 votes

The given equation is


4x-2x+8=6(x+4)

First, we reduce like terms and use the distributive property.


2x+8=6x+24

Now, we subtract 6x on each side.


\begin{gathered} 2x+8-6x=6x+24-6x \\ -4x+8=24 \end{gathered}

Then, we subtract 8 on each side.


\begin{gathered} -4x+8-8=24-8 \\ -4x=16 \end{gathered}

At last, we divide the equation by -4.


\begin{gathered} (-4x)/(-4)=(16)/(-4) \\ x=-4 \end{gathered}

Therefore, the solution is -4.e, the so

User KevBry
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.